Nepalese Foreign Trade: Growth, Composition, and Direction - Acharya, Khubi Ram (NCC Journal, 2019)
The objective of this article is to study and analyze the growth, composition, and direction of the Nepalese foreign trade. This is descriptive a study that uses secondary sources of information. The analysis is based on simple statistical tools like ratio and percent. This study finds the very low export performance of Nepal. This is creating the problem of rapidly increasing trade deficit. Nepal is also unable to diversify its trade in terms of countries and commodities. The major causes of increasing trade deficit are low export, and high import, low-quality products, improper trade policy, higher cost of production, lack of publicity and advertisement, low production, slow industrial development, lack of trade diversification, etc. Nepal can reduce its trade deficit by diversification of its trade in terms of commodities and countries.